2001
DOI: 10.1038/sj.jhh.1001282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quality of life and cough on eprosartan and enalapril in people with moderate hypertension

Abstract: The objective of this study was to compare quality of life and incidence of dry persistent cough among patients treated with eprosartan and enalapril for mild-moderate hypertension. This was a randomised 26-week doubleblind controlled trial carried out in clinics in nine countries of North America, Europe and South Africa. A total of 529 patients aged 18 and over with diastolic blood pressure between 95 mm Hg and 114 mm Hg were studied. Treatment comprised of eprosartan or enalapril monotherapy for 12 weeks wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Estimates suggest that around 10% of patients develop cough with ACE inhibitor therapy, and that it may lead to treatment withdrawal in approximately half of these patients [27,28]. The occurrence of ACE inhibitor-induced cough may impact on patient quality of life [28], although some studies suggest that it has little effect on patient well being [29,30]. Headache was more frequent with aliskiren than ramipril therapy, although the proportion of events considered to be related to study medication was low and similar in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates suggest that around 10% of patients develop cough with ACE inhibitor therapy, and that it may lead to treatment withdrawal in approximately half of these patients [27,28]. The occurrence of ACE inhibitor-induced cough may impact on patient quality of life [28], although some studies suggest that it has little effect on patient well being [29,30]. Headache was more frequent with aliskiren than ramipril therapy, although the proportion of events considered to be related to study medication was low and similar in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the present study, we have shown than eprosartan alone or in combination with a diuretic can be effective in reducing SBP in elderly patients with ISH. While a cost analysis is beyond the purview of this manuscript, the lack of persistent cough (as seen with ACE inhibitors), 18 lack of drug interaction, 19 and once-a-day dosing, are additional benefits of eprosartan use. For patients who do not respond to eprosartan alone, the simple addition of a diuretic may be additive and suffice to decrease SBP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Only 9 studies, described in 13 publications (27,29,31,38,41,44,46,48,49,59,62,65,79), reported how many patients died or had myocardial infarction or stroke ( Table 2). Most of these studies excluded patients with clinically significant cardiovascular disease and other comorbid conditions.…”
Section: Death and Major Cardiovascular Eventsmentioning
confidence: 99%
“…Four fair-quality studies described in 8 papers reported quality-of-life outcomes (27, 31,35,38,41,43,48,76). They used a variety of quality-of-life scales.…”
Section: Quality Of Lifementioning
confidence: 99%